Mechanical properties of tapioca starch edible films containing sorbates - Fama, Lucia Mercedes (2005)
The effect of sorbate present on mechanical properties of edible films prepared with suspensions of tapioca starch containing glycerol, was studied. Films were prepared by casting the systems after gelatinization. The storage modulus (E′) and the tangent of the phase angle (tan δ) of the film pieces were determined with a Dynamic Mechanical Thermal Analyzer along 8 weeks of storage at a relative humidity (RH) of 57.5% and at 25°C. Stress-strain behavior along quasi-static tests was also analysed using the same device. Results obtained showed that sorbate incorporation resulted in a decrease (≅75%) of E′ and an increase (≅200%) of tan δ after 2 weeks of storage. Antimicrobial presence also affected film performance along storage: it showed a continuous decrease of tan δ along 8 weeks storage as well as an increase in the tendency to rupture with time. Films without sorbate showed an increase of tan δ along 4 weeks and they presented rupture for all storage periods studied. Aging of starch, characteristics of the network as well as sorbate destruction along storage, are responsible for the changes observed in mechanical properties of the film along 8 weeks. © 2004 Swiss Society of Food Science and Technology. Published by Elsevier Ltd. All rights reserved.